2014
DOI: 10.1002/anie.201402752
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Ethanolysis of Kraft Lignin into High‐Value Small‐Molecular Chemicals over a Nanostructured α‐Molybdenum Carbide Catalyst

Abstract: We report the complete ethanolysis of Kraft lignin over an α-MoC1-x /AC catalyst in pure ethanol at 280 °C to give high-value chemicals of low molecular weight with a maximum overall yield of the 25 most abundant liquid products (LP25) of 1.64 g per gram of lignin. The LP25 products consisted of C6 -C10 esters, alcohols, arenes, phenols, and benzyl alcohols with an overall heating value of 36.5 MJ kg(-1) . C6 alcohols and C8 esters predominated and accounted for 82 wt % of the LP25 products. No oligomers or ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
207
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(222 citation statements)
references
References 26 publications
12
207
2
1
Order By: Relevance
“…It was speculated that the basic conditions favoured the formation of phenolate products, whose superior solvation inhibited their subsequent absorption and hydrogenation. Molybdenum catalysts have also been studied for lignin depolymerization over different supports, including alumina and carbon [38,39]. Ma et al reported lignin depolymerization in supercritical ethanol over Mo/Al 2 O 3 and the optimum reduction temperature evaluated and identified as 750°C.…”
Section: Hydrogenolysismentioning
confidence: 99%
See 1 more Smart Citation
“…It was speculated that the basic conditions favoured the formation of phenolate products, whose superior solvation inhibited their subsequent absorption and hydrogenation. Molybdenum catalysts have also been studied for lignin depolymerization over different supports, including alumina and carbon [38,39]. Ma et al reported lignin depolymerization in supercritical ethanol over Mo/Al 2 O 3 and the optimum reduction temperature evaluated and identified as 750°C.…”
Section: Hydrogenolysismentioning
confidence: 99%
“…Lignin was converted into a complex mixture of low molecular weight compounds, such as aliphatic alcohols, C 8 -C 10 esters, monophenols, benzyl alcohols, and arenes [39]. The same authors reported that nanostructured Mo x C achieved complete catalytic ethanolysis of Kraft lignin in supercritical ethanol under N 2 at 280°C [38]. Hydrogen pressure exerted a moderate influence on the yield of liquid products, increasing alcohol production at the expense of esters.…”
Section: Hydrogenolysismentioning
confidence: 99%
“…This methodology consists of treating a Mo precursor under continuous H2/hydrocarbon flow of differing compositions and different temperatures. This technique has been largely utilized to produce unsupported and supported molybdenum carbides [32,33]. Djéga-Mariadassou and coworkers studied the sequential transformation of the crystal structure of the oxide precursor from molybdic acid to Mo4O11 to MoO2 to Mo to Mo2C, by X-ray diffraction (XRD) [34].…”
Section: Temperature-programmed Reduction (Tpr)mentioning
confidence: 99%
“…Kraft lignin was also converted by Ma and coauthors into C 6 -C 10 chemicals at high-yield without any tar or char formation over a nanostructured α-molybdenum carbide catalyst [33]. Ethanolysis of the Kraft lignin in supercritical ethanol without the addition of gaseous hydrogen took place over an activated carbon-supported α-molybdenum carbide (α-MoC 1−x /AC) catalyst.…”
Section: Ligninmentioning
confidence: 99%
“…Similar phenolic compounds were observed in the depolymerization of Norway spruce lignin in a supercritical ethanol/formic acid mixture at 380 ºC for 54 h (Kleinert and Barth 2008), non-catalytic cracking of pyrolytic lignin in supercritical ethanol at 260 ºC for 8 h (Tang et al 2010), hydro-processing of organosolv lignin in supercritical ethanol using Ru/C-Al2O3 as a catalyst at 260 ºC for 8 h (Patil et al 2011), depolymerization of kraft lignin in supercritical ethanol using CuMgAlOx as a catalyst at 300 ºC for 4 h (Huang et al 2014), and catalytic ethanolysis of kraft lignin using Mo2C/AC at 280 ºC for 6 h (Ma et al 2014). Based on this research, the use of a catalyst can reduce the reaction temperature of lignin depolymerized in supercritical ethanol, while the regulation mechanisms of the catalyst on the depolymerization reaction of lignin in sub-and super-critical ethanol are not clearly understood.…”
Section: Introductionmentioning
confidence: 99%